Pengaruh Tingkat Pemahaman Pajak, Kualitas Pelayanan Publik, Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Roda Dua Di DKI Jakarta (Studi Kasus Pengendara Ojek Online) - Cindy Apriani Chandra, Rizka Indri Arfianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
Motor Vehicle Tax is a motor vehicle that can be used for two-wheeled motor vehicles or more. Based on data obtained from the DKI Jakarta Regional Tax and Retribution Agency, the plan for the acceptance of Vehicle Tax is expected to be higher every year, but at the time of the realization of the DKI Jakarta Provincial Motor Vehicle Tax receipts the discrepancy between the plan and the realization. The purpose of this research are To know if understanding of taxation, the quality of public tax, and tax penalties effects tax compliance of two-wheeled motor vehicle taxpayers. This research uses multiple regression analysis method. Data and information obtained from the questionnaires filled out by 100 respondents who works as ojek online driver in DKI Jakarta.Â The test method is performed using Likert Scale; Software SPSS 20; Validity and Reliability Test; F Test; t Test; R2 Test and the classical Assumption Test. The results of this study indicate that (1) There is no enough evidence that the understanding of taxation effects tax compliance of two-wheeled motor vehicle taxpayers. (2) There is evidence that the quality of public tax services affects tax compliance of two-wheeled motor vehicle taxpayers. (3) There is no evidence tax penalties effects tax compliance of two-wheeled motor vehicle taxpayers.Keywords: Understanding of Taxation, The Quality of Public Tax Services, Tax Penalties, Tax Compliance